BUILDING PROFESSIONALISM THROUGH SENSE OF BELONGING AND POSITIVE CHARACTER - Elvie Maria; Josep Yuki Hartandi; Brilliant Handyman Manalu; Andriasan Sudarso (Jurnal Abdisci, 2026)
Introduction. The VUCA era (Volatility, Uncertainty, Complexity, and Ambiguity) poses substantial challenges to the professionalism of educators and educational personnel, which can no longer depend solely on technical competencies, formal regulations, and structural supervision. These conditions necessitate a form of professionalism grounded in internal awareness, character resilience, and a clear value orientation. T Purpose. This article aims to conceptually examine the role of sense of belonging and positive character as fundamental foundations in fostering educator professionalism within the educational sector in the context of the VUCA era. Method. Using a conceptual framework and systematic literature review, the study explores how educators' psychological attachment to institutional values, vision, and identity contributes to the internalization of positive character traits, including integrity, responsibility, commitment, and exemplary conduct. Result and discussion. Sense of belonging is conceptualized as a psychological mechanism that enhances the consistency of educators' professional behavior amid policy uncertainty, role complexity, and ambiguity in educational practice. The analysis indicates that value- and character-based professionalism demonstrates greater sustainability and adaptability than professionalism driven primarily by procedural compliance. Conclusion. This article implicitly argues that strengthening sense of belonging and positive character represents a strategic approach to developing adaptive, reflective, and meaningful educator professionalism in the VUCA era, with important implications for educational policy development and professional practice.